The apprentice years: Shirley Geok-lin Lim's "First" interview - Quayum, Mohammad Abdul (IIUM Press, International Islamic University Malaysia, 2017)
An interview with the Malaysian-American poet-writer Shirley Geok-lin Lim that traces her early career, from the beginning to the years after she received the prestigious Commonwealth Writers Prize in 1980. Although Lim is a versatile writer who has excelled in multiple genres, this interview focuses exclusively on her poetry as her primary calling as a writer has been that of a poet. In the interview, Lim explains her challenges and accomplishments in the early years, especially as a migrant poet in the US, and highlights the various methods and techniques she used in her early poetry.